Początkowy okres formowania i służby 2 Oddziału Ochrony Pogranicza na zachodniej granicy Polski w latach 1945-1946 = The initial period of forming and service of the 2nd Border Guard Division on the western border of Poland - Trojanowski, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
2nd Division of Border Guard Forces was the only border formation issued in the Poznań Military District. 4 October 1945 is considered to be the commencement date of its formation. On this day, Lt. Col. Stanisław Dobrzański came to Poznań and he was appointed acting commander of the created unit.
Keywords: Wojska Ochrony Pogranicza; pogranicze; historia wojskowości; początki władzyludowej; the border protection forces; borderland; history of military; the beginnings of people?s authority